Penanaman Nilai-Nilai Religius Dalam Membentuk Akhlak Karimah Bagi Peserta Didik Di Mi Ar-Rahim Kecamatan Arjasa Kabupaten Jember - Agus Zainudin (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
The industry of era 4.0 has an impact on competitive advantage to life aspects. In the context of education, being competitive to get the best education in academic achievement has become a kind of competition. This is where the demands and expectations of some users of education emerge to bring about human excellence through the concept of moral in the world of education. Moral character can be formed if humans respect each other and carry out their religious teachings with pure and consistent. Religious values ​​are important values ​​to be instilled to students because these values ​​will be able to make students become more exemplary, tolerant and more religious and even practice their religious teachings and touch their affection and psychomotor. This scientific article discusses the cultivation of religious values ​​by forming religious culture so that eventually students will get used to practicing religious values ​​and will become learners who respect each other even with other religions and have a moral character